Pengaruh Cognitive Behavioral Therapy Terhadap Self Efficacy dan Self Care Behavior Pasien Hipertensi di Kota Palangka Raya - Gad Datak; Ester Inung Sylvia; Alfeus Manuntung (Jurnal Surya Medika (JSM), 2018)
Nurse as educator and counselor for patients can provide assistance to patients in the form of the supportive-educative system by providing health education or counseling with the goal of treatment of hypertension patients were able to perform independently. One technique used counseling is Cognitive Behavioral Therapy (CBT) which is an approach to psychotherapy that is used to handle the emotions dysfunctional, maladaptive behaviors and cognitive processes and contents through goal-oriented, systematic procedure explicit. This study aims to determine the effect of Cognitive Behavioral Therapy (CBT) against self-efficacy and self-care behavior of patients with hypertension in the city of Palangkaraya. The design used in this study is a quasi-experiment with the non-randomized study design pretest-posttest control group design. Sampling techniques in this study were consecutive sampling, 12 patients with hypertension in the puskesmas Kayon, the city of Palangkaraya as the intervention group and 12 patients with hypertension in the puskesmas Panarung, the city of Palangkaraya as a control group. The results showed that Cognitive Behavioral Therapy (CBT) significantly improve self-efficacy of patients with hypertension in the city of Palangkaraya (p = 0.000) and also improve self-care behavior of patients with hypertension in the city of Palangkaraya (p=0.000) Recommendations of the results of this study is Cognitive Behavioral Therapy (CBT) can be used as action by nurses in puskesmas through home visits to patients with hypertension to reduce complications of the disease and improve the quality of life of patients hypertension.